1992
DOI: 10.1007/bf00172660
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral leukemic mass in acute myelogenous leukemia

Abstract: Leukemic intracranial space occupying lesions are rare. A 69 year old man with acute myelogenous leukemia was found to have an intracranial leukemic mass at the time of his remission period. Computed tomography and magnetic resonance imaging study demonstrated a large irregular mass in the right temporal lobe. After total removal of the tumor, the patient was treated with whole brain irradiation and intrathecal chemotherapy. After surviving for 7 months, the patient expired of hematologic relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…13) Review of eight reported cases concluded that immediate prophylactic systemic chemotherapy for granulocytic sarcoma during bone marrow remission would lead to favorable outcomes. 38) Our patient received systemic chemotherapy and whole neural axis irradiation, and achieved complete remission.…”
Section: Discussionmentioning
confidence: 99%
“…13) Review of eight reported cases concluded that immediate prophylactic systemic chemotherapy for granulocytic sarcoma during bone marrow remission would lead to favorable outcomes. 38) Our patient received systemic chemotherapy and whole neural axis irradiation, and achieved complete remission.…”
Section: Discussionmentioning
confidence: 99%
“…The most common sites of involvement are the bone, periosteum, soft tissue, lymph nodes and skin (6)(7)(8)(9). It is often seen in perineural and epidural structures causing compression of the central and peripheral nervous system (10)(11)(12). GS …”
Section: Discussionmentioning
confidence: 99%
“…Despite of the rarity, the meninges represent an important site of relapse [9]. Regarding intracerebral masses, they are sometimes seen as a complication of acute myelogenous leukemia [10].…”
Section: Introductionmentioning
confidence: 99%